PWE-161 The Macrogol Drink Test To Distinguish Functional Constipation (fc) And Constipation Predominant Irritable Bowel Syndrome (ibs-c): Underlying Mechanisms Demonstrated Using Mri. (9th June 2014) - Lam, C; Chaddock, G; Hoad, C; Costigan, C; Cox, E; Pritchard, S; Garsed, K; Marciani, L; Gowland, P; Spiller, R
Abstract : Introduction: Patients with constipation may have either FC or IBS-C which require different treatments. They are often dissatisfied with their treatment because diagnosis relies on symptoms which frequently overlap. Methods: 46 CC patients (24 FC and 22 IBS-C), age 18–68 years, unresponsive to simple laxatives, were compared with 11 healthy volunteers (HV). Whole gut transit (WGT) was assessed using a MRI scan 24 h following ingestion of 5 marker pills as previously validated. Patients then consumed 1 litre of macrogol (MCG) followed by hourly MRI scans for 4 h and scored bowel symptoms from 0–10 (none-severe). Colonic movements were assessed using a motility index (MI) based on colonic wall movement and hypersensitivity index (HI) was calculated as bloating symptom/ascending colon (AC) volume. Results: Mean (SD) See Table 1 . FC and IBS-C have slower WGT and higher HI than HV. FC showed significantly greater fasting SBWC, AC volume and reduced MI following ingestion of MCG compared to HV and IBS-C. Moreover, FC showed impaired response to MCG with longer time to first bowel movement and reduced stool frequency on the study day when compared with HV and IBS-C. Time to 1st bowel movement correlated significantly with AC volume 2h post MCG, r = 0.44, p = 0.004 and fasting SBWC, r = 0.34, p = 0.035. Using a cut-off >230 min distinguishes FC from IBS-C with sensitivity 55% and specificity 95%; this needs validation in a repeat study. Conclusion: Time to first bowel movement >230 min makes IBS unlikely and should help target treatments. Our MI studies show this is dueto greater motility response to distension in IBS-C who has lower fasting SBWC and AC volumes versus FC. IBS-C showed similar features to HV but can be distinguished by greater HI following distension which suggest hypersensitivity. This inexpensive test done without MRI could help clinicians to distinguish these 2 conditions. Disclosure of Interest: C. Lam: None Declared, G. Chaddock: None Declared, C. Hoad: None Declared, C. Costigan: None Declared, E. Cox: None Declared, S. Pritchard: None Declared, K. Garsed: None Declared, L. Marciani: None Declared, P. Gowland Consultant for: Merck, Ironwood, Unilever, R. Spiller Grant/research support from: Lessaffre, Ironwood, Consultant for: Almirall, Astellas, Danone and Sanofi, Conflict with: Free drug for clinical trial from Norgine.